Cover Picture: LEGO‐NMR Spectroscopy: A Method to Visualize Individual Subunits in Large Heteromeric Complexes (Angew. Chem. Int. Ed. 43/2013). Issue 43 (2nd October 2013) - Mund, Markus; Overbeck, Jan H.; Ullmann, Janina; Sprangers, Remco
<x xml:space="preserve">Abstract</x> Large asymmetric assemblies are difficult to prepare recombinantly and result in complicated NMR spectra that cannot be analyzed in detail. Both issues are addressed simultaneously in the LEGO‐NMR method described by R. Sprangers and co‐workers in their Communication on page 11401 ff. The method is based on sequential co‐expression of NMR active and NMR invisible protein subunits of a large assembly and significantly simplifies both amide backbone and methyl side‐chain spectra.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>